2020
DOI: 10.1111/ejh.13368
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with brentuximab vedotin plus bendamustine in unselected patients with CD30‐positive aggressive lymphomas

Abstract: Objectives A treatment regimen consisting of bendamustine and brentuximab vedotin (BV) has been described as a highly potent salvage therapy and as an effective induction therapy leading to high response rates before autologous stem cell transplantation (ASCT) in patients with classical Hodgkin lymphoma (cHL). In this retrospective analysis, we aimed to assess this therapy's efficacy in unselected patients with cHL and CD30+ peripheral T‐cell lymphoma (PTCL). Patients and methods Data of 28 patients with cHL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Single‐agent bendamustine achieved a CMR rate of 33% in adults with R/R cHL 5 . While there are no randomised comparisons, a number of studies have reported higher CR/CMR rates with the combination of Bv plus bendamustine (Bv + B) in adults, than with either agent alone 2,6–11 . A phase 1/2 study of 55 adults with R/R cHL reported a CR rate of 74%, with PFS at three years of 60%, in patients undergoing ASCT 6 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Single‐agent bendamustine achieved a CMR rate of 33% in adults with R/R cHL 5 . While there are no randomised comparisons, a number of studies have reported higher CR/CMR rates with the combination of Bv plus bendamustine (Bv + B) in adults, than with either agent alone 2,6–11 . A phase 1/2 study of 55 adults with R/R cHL reported a CR rate of 74%, with PFS at three years of 60%, in patients undergoing ASCT 6 .…”
Section: Figurementioning
confidence: 99%
“…5 While there are no randomised comparisons, a number of studies have reported higher CR/CMR rates with the combination of Bv plus bendamustine (Bv + B) in adults, than with either agent alone. 2,[6][7][8][9][10][11] A phase 1/2 study of 55 adults with R/R cHL reported a CR rate of 74%, with PFS at three years of 60%, in patients undergoing ASCT. 6 However, a retrospective series using Bv + B in children and young people reported a lower CR rate of 43%, and two-year PFS of 33%.…”
mentioning
confidence: 99%
“…Kim et al [90] reported that the disease control rate was 48.5% in the patients with R/R high CD30-expressing NHL including PTCL-NOS (24.2%), ENKTL (21.2%) and AITL (3%). Recently, Wagner et al [91] suggested that a combination of bendamustine and BV may be an effective salvage therapy in patients with PTCL. Together, the data from clinical trial suggest that BV has opened a new era in the management of PTCL.…”
Section: Targeting Cell Surface Moleculesmentioning
confidence: 99%
“…The current trend is a combination of this drug with other drugs in order to reach a synergistic effect and a better therapeutic index. The example of this approach is a combination with an alkylation agent bendamustine (Treanda) in induction therapy prior to autologous stem cell transplantation in patients with Hodgkin’s lymphoma [ 176 ].…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%